The Effect of Job Involvement, HR Development Programs, and Work Motivation on Employee Job Satisfaction - Amalina Apriyan Della Nabella; Audita Nuvriasari (LifeSciFi, 2025)
In the context of increasing business competition, employee job satisfaction plays a crucial role in supporting organizational sustainability and performance. Job satisfaction is influenced by several internal factors, including job engagement, human resource development programs, and work motivation. This study aims to analyze the influence of job engagement, human resource development programs, and work motivation on employee job satisfaction at PT Habbie Bangun Aromatik. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees and analyzed using statistical techniques. The results showed that job engagement and human resource development programs had a positive but insignificant effect on employee job satisfaction. Conversely, work motivation showed a significant effect on job satisfaction. These findings suggest that employee work motivation in their work is a major determinant of job satisfaction. Therefore, it is concluded that management should focus on strengthening employee work motivation to improve employee job satisfaction and support organizational performance.